Investigating the Effects of Acupressure and Auriculotherapy on Anxiety During Labor, Neonatal Outcomes, and Maternal-fetal Attachment: A Systematic Review and Meta-analysis - Maryam Mirzaei; Vahideh Hafezi Siahlarz; Sara Saadat; Firoozeh Mirzaee; Malihe Afiat Milad; Masumeh Ghazanfarpour (Mazandaran University of Medical Sciences, 2024)
Background: Divergent findings reported in the literature on the impact of acupressure on improvement in mothers' anxiety during labor and consequently on birth outcomes. However, there is no existing meta-analysis on this issue. Objectives: This systematic review assesses the effect of acupressure and auriculotherapy on anxiety during labor, neonatal outcomes, and maternal-fetal attachment. Methods: The Cochrane central register of controlled trials, MEDLINE/PubMed, ISI, and Scopus online databases were searched by two researchers up to January 2023. The quality of studies was assessed based on the Jade scale. Results: Nine studies were included in the systematic review and meta-analysis. Acupressure significantly decreased anxiety compared to touching (standardized mean difference=-3.29; P<0.001; I2=8%; P=0.295; the fixed effect model) and routine care (standardized mean difference=-1.08; confidence interval=-2.46 to 0.30; P=0.12; I2=96.19%; P<0.001). Maternal-fetal attachment was higher in both groups who received acupressure and auriculotherapy compared to the control group (P<0.001). Meanwhile, auriculotherapy did not impact neonatal outcomes, such as newborns' weight and Apgar score. Conclusions: Acupressure was an effective tool to improve anxiety during labor and it consequently improved fetal oxygenation.